2021
DOI: 10.3389/fpubh.2021.606364
|View full text |Cite
|
Sign up to set email alerts
|

High-Minority Nursing Homes Disproportionately Affected by COVID-19 Deaths

Abstract: Racial/ethnic disparities in healthcare have been highlighted by the recent COVID-19 pandemic. Using the Centers for Medicare and Medicaid Services' Nursing Home COVID-19 Public File, this study examined the relationship between nursing home racial/ethnic mix and COVID-19 resident mortality. As of October 25, 2020, high minority nursing homes reported 6.5 COVID-19 deaths as compared to 2.6 deaths for nursing homes that had no racial/ethnic minorities. After controlling for interstate differences, facility-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…With one exception, 27 all studies used facility-level data and did not control for resident-level risk factors. Thirty-four studies examined nursing homes only, [31][32][33][34][35][36][37][38][39][40][41][42][43] one study included nursing homes and ALCs, 29 and one study examined ALCs only. 30 Nine were single-state studies; 11,15,18,[21][22][23]25,27,29 14 were national studies; 10,14,17,19,20,24,31,[36][37][38][40][41][42][43] and the remainder were multi-state studies including between 3 and 30 states.…”
Section: Resultsmentioning
confidence: 99%
“…With one exception, 27 all studies used facility-level data and did not control for resident-level risk factors. Thirty-four studies examined nursing homes only, [31][32][33][34][35][36][37][38][39][40][41][42][43] one study included nursing homes and ALCs, 29 and one study examined ALCs only. 30 Nine were single-state studies; 11,15,18,[21][22][23]25,27,29 14 were national studies; 10,14,17,19,20,24,31,[36][37][38][40][41][42][43] and the remainder were multi-state studies including between 3 and 30 states.…”
Section: Resultsmentioning
confidence: 99%
“…NHs serving a high proportion of minorities are known to have fewer resources, lower quality of care, 27 and have experienced more COVID-19 cases and deaths than low-minority NHs. 28 , 29 , 30 , 31 To date, there is no empirical study on how the pandemic influenced antipsychotic use in NHs serving a high- versus low-proportion of minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Narrowing the focus to age and race, the elderly and children were even more vulnerable to infection. The early days of the pandemic showed that elderly populations were highly vulnerable to infection, with nursing homes that cared for larger populations of non-white residents reporting increased infection rates and deaths weekly ( Li et al, 2020 ; Weech-Maldonad et al, 2021 ). Additionally, nursing home facilities with higher rates of non-white residents faced COVID-19 death rates that were 3.3 times higher than facilities with higher proportions of white elderly residents.…”
Section: Overviewmentioning
confidence: 99%